From ultrafast to slow: Heating rate dependence of the glass transition temperature in metallic systems. (1st December 2016) - Küchemann, Stefan; Gibbins, Goodwin; Corkerton, Joe; Brug, Eleanor; Ruebsam, Jonas; Samwer, Konrad
Abstract : When a solid crosses the glass transition, viscous flow sets in and the glass transforms into a supercooled liquid. The glass transition temperature exhibits a heating rate dependence which was previously observed to follow a Vogel–Fulcher–Tammann (VFT) equation. Here we report on a change in the heating rate dependence of the glass transition, determined by the distinct increase in the specific heat capacity, of a metallic glass. We combine standard techniques such as differential scanning calorimetry with recently developed ohmic heating techniques in order to cover seven orders of magnitude in heating rate. Contrary to previous reports, our results show that the change of the glass transition temperature cannot be described by a single VFT equation. Instead we find two distinct regimes which independently follow a VFT expression.